A Novel Technique of Ultra-Mini-Percutaneous Nephrolithotomy: Introduction and an Initial Experience for Treatment of Upper Urinary Calculi Less Than 2 cm. (24th July 2013) - Desai, Janak; Zeng, Guohua; Zhao, Zhijian; Zhong, Wen; Chen, Wenzhong; Wu, Wenqi
Abstract : Objectives . To describe our novel modified technique of ultra-mini-percutaneous nephrolithotomy (UMP) using of a novel 6 Fr mininephroscope through an 11–13 Fr metal sheath to perform holmium: YAG laser lithotripsy. Methods . The medical records of 36 patients with moderate-sized (<20 mm) kidney stones treated with UMP from April to July 2012 were retrospectively reviewed. Patients were assessed at the 1st day and 1st month postoperatively by KUB and US to assess stone-free status. Results . The mean stone size was 14.9 ± 4.1 mm (rang: 6–20). The average operative time was 59.8 ± 15.9 (30–90) min. The stone-free rate at postoperative 1st day and 1st month was 88.9% and 97.2%. The mean hospital stay was 3.0 ± 0.9 (2–5) days. Complications were noted in 6 (16.7%) cases according to the Clavien classification, including sepsis in 2 (5.6%) cases (grade II), urinary extravasations in 1 (2.8%) case (grade IIIa), and fever in 3 (8.3%) cases (grade II). No patients needed blood transfusion. Conclusions . UMP is technically feasible, safe, and efficacious for moderate-sized renal stones with an advantage of high stone-free rates and low complication rates. However, due to the limits of its current unexplored indications, UMP is therefore a supplement to, not a substitute for, the standard mini-PCNL technology.